2005
DOI: 10.1111/j.1523-1755.2005.00392.x
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive response to prolonged tempol in the spontaneously hypertensive rat

Abstract: Tempol corrects hypertension without a compensatory sympathoadrenal activation or salt retention. The response is independent of nitric oxide, endothelin, or catecholamines and occurs despite increased PRA. It is accompanied by a reduction in oxidative stress and is maintained during increased salt intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
68
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(74 citation statements)
references
References 44 publications
(64 reference statements)
6
68
0
Order By: Relevance
“…This may be explained on the basis of the inhibition of angiotensin converting enzyme by exogenous H 2 S 47 and the superoxide scavenging activity of exogenously administered tempol. 13,48 It was observed that although both H 2 S and tempol functions in an independent way, the interaction of the two groups results in a greater response. However, the reductions in blood pressure and increased renal excretion observed in the present study after the combination therapy with exogenous H 2 S and tempol are neither additive nor potentiating in a true sense as was hypothesized.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This may be explained on the basis of the inhibition of angiotensin converting enzyme by exogenous H 2 S 47 and the superoxide scavenging activity of exogenously administered tempol. 13,48 It was observed that although both H 2 S and tempol functions in an independent way, the interaction of the two groups results in a greater response. However, the reductions in blood pressure and increased renal excretion observed in the present study after the combination therapy with exogenous H 2 S and tempol are neither additive nor potentiating in a true sense as was hypothesized.…”
Section: Discussionmentioning
confidence: 99%
“…17,27 In terms of the chronic tempol administration, its antioxidant action 12 is also partly responsible for the reduction in blood pressure which would be in accord with previous reports. 13,18 Moreover, the co-treatment with NaHS and tempol resulted in a significantly greater decrease in systolic blood pressure and mean arterial blood pressure compared with the SHR + NaHS and SHR + tempol groups. Taken together, this suggests that the reductions in blood pressure in the SHR following the combination of NaHS and tempol may be influenced by both the antioxidant activity of tempol 13 and the up-regulation of the CSE enzyme by exogenous NaHS resulting in increased production of endogenous H 2 S. 18 Supporting this argument, there was a marked increase in plasma H 2 S levels and urinary H 2 S excretion.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations